The impact of Islamic financial literacy on Islamic financial planning of Islamic university students - Aisyah, Muniaty; Umiyati, Umiyati; Suzanawaty, Leis (LPPM ISNJ Bengkalis, 2025)
Purpose – This study aims to analyze the influence of Islamic university students' Islamic financial literacy on their Islamic financial planning. Method – This study uses a quantitative approach with convenience sampling and a Structural Equation Model - Partial Least Square (SEM-PLS) analysis technique. This study analyzed 110 primary data sets using the Smart PLS application. Representing the population of Islamic university students, the sample or respondents were students from the Islamic banking study program at Syarif Hidayatullah State Islamic University Jakarta, one of Indonesia's largest state Islamic universities. Findings – The results show that students' Islamic financial knowledge and behavior positively affect Islamic financial planning, while students' Islamic financial attitudes have no effect. Implications – Theoretically, this study can complement existing theories, especially the influence of Islamic financial knowledge and behavior on Islamic financial planning. Practically, this study can be a reference in improving Islamic financial literacy and planning of Islamic university students, especially regarding Islamic financial knowledge and behavior.